Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/jwmg.21126
|View full text |Cite
|
Sign up to set email alerts
|

Searcher efficiency and survey coverage affect precision of fatality estimates

Abstract: Studies at renewable energy sites often attempt to estimate avian and bat fatalities or fatality rates (e.g., fatalities/megawatt [MW]/year). However, searcher efficiency and level of survey effort among sites are variable. We evaluated how searcher efficiency and proportion of area surveyed affected precision of fatality estimates and probability of detecting rare fatalities (e.g., fatalities of an endangered species). We measured searcher-efficiency rates of human and dog-handler teams for 3 fatality types: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Multiple steps can be taken to detect more of the available fatalities, including searching to a maximum radius around wind turbines that includes the majority of deposited carcasses, searching along transects spaced closer together, searching more frequently, and searching with skilled detection dogs instead of only humans. Homan et al (2001), Arnett (2006), Paula et al (2011), and Matthews et al (2013) reported that using skilled dogs greatly increased carcass detection rates over human searchers, and Reyes et al (2016) reported that dogs improved searcher efficiency and were more likely to detect fatalities of rarely represented species.…”
mentioning
confidence: 99%
“…Multiple steps can be taken to detect more of the available fatalities, including searching to a maximum radius around wind turbines that includes the majority of deposited carcasses, searching along transects spaced closer together, searching more frequently, and searching with skilled detection dogs instead of only humans. Homan et al (2001), Arnett (2006), Paula et al (2011), and Matthews et al (2013) reported that using skilled dogs greatly increased carcass detection rates over human searchers, and Reyes et al (2016) reported that dogs improved searcher efficiency and were more likely to detect fatalities of rarely represented species.…”
mentioning
confidence: 99%
“…To obtain cabin data, we invested the recording time (an observer for 33 days of round trips) and the time for review and assembly of the data (an ornithologist working for about 50 days). In comparison, field data collection in the two sub-stretches of rail line required a group of at least three ornithologists and one safety technician during 48 days (4 seasons * 6 surveys * 2 sub-stretches) as well as parallel installation of baited stations to estimate carcass removal rates and carcass detectability (Reyes et al, 2016). Added to these resources, would be preparation time for field material and datasets (total of around 24 person-days).…”
Section: Discussionmentioning
confidence: 99%
“…The infrastructure is fenced and highly restricted to human access for safety reasons, making it very difficult to run field studies (Wells et al, 1999). Also, bird carcasses from train collisions are left in a condition which makes location and identification difficult, especially in the presence of scavenger animals around railways (Heske, 2015;Reyes et al, 2016). Besides, the sheer breadth of rail networks and cost of fieldwork make it practically impossible to conduct studies that cover even a small part of a network.…”
Section: Introductionmentioning
confidence: 99%
“…Wind facility carcass search detection probabilities are complicated because they depend on the timing of seasonal carcass arrivals, search start date, search end date, search interval, number of searched turbines, searcher efficiency (detection given presence), carcass removal rates, and the proportion of the carcasses that fall in the searched area. Here, we rely on established formulas implemented in the genest R package (west-inc.shinyapps.io/GenEst/; cran.r-project.org/GenEst) to compute detection probabilities and variation given study design elements Reyes et al, 2016). Whether using genest or not, we assume field data collection elements have been evaluated and that site-specific and have been computed.…”
Section: Eoar Model Definitionmentioning
confidence: 99%